Effects of the injection parameters on the emissions of a heavy duty diesel engine - (:unkn) unknown (American Society of Mechanical Engineers (ASME), 2010)
It is estimated by the experts in the automotive industry that diesel engines on the transport market should increase within the years to come due to their high thermal efficiency coupled with low carbon dioxide (CO2) emissions, provided their nitrogen oxides (NOx) and particulate emissions are reduced. At present, adequate after-treatments, NOx and particulates matter (PM) traps are developed and industrialized with still concerns about fuel economy, robustness, sensitivity to fuel sulfur and cost because of their complex and sophisticated control strategy. New combustion processes focused on clean diesel combustion are investigated for their potential to achieve near zero particulate and NOx emissions. Their main drawbacks are increased level of unburned hydrocarbons (HC) and carbon monoxide (CO) emissions, combustion control at high load and limited operating range and power output. In this work, cold flow simulations for a single cylinder of a nine-liter (6 cylinder x 1.5 It.) diesel engine have been performed to find out flow development and turbulence generation in the pistoncylinder assembly. In this study, the goal is to understand the flow field and the combustion process in order to be able to suggest some improvements on the in-cylinder design of an engine. Therefore combustion simulations of the engine have been performed to find out flow development and emission generation in the cylinder. Moreover, the interaction of air motion with high-pressure fuel spray injected directly into the cylinder has also been carried out. A Lagrangian multiphase model has been applied to the in-cylinder spray-air motion interaction in a heavy-duty CI engine under direct injection conditions. A comprehensive model for atomization of liquid sprays under high injection pressures has been employed. The combustion is modeled via a new combustion model ECFM-3Z (Extended Coherent Flame Model) developed at IFP. Finally, a calculation on an engine configuration with compression, spray injection and combustion in a direct injection Diesel engine is presented. Further investigation has also been performed incylinder design parameters in a DI diesel engine that result in low emissions by effect of high turbulence level. The results are widely in agreement qualitatively with the previous experimental and computational studies in the literature. Copyright © 2010 by ASME.
Keywords: CFD; Clean diesel combustion; Combustion; Spray